Use, marketing, and appeal of oral nicotine products among adolescents, young adults, and adults. (May 2023) - Gaiha, Shivani Mathur; Lin, Crystal; Lempert, Lauren Kass; Halpern-Felsher, Bonnie
Highlights: Adolescents, young adults, and adults are increasingly using oral nicotine products including nicotine pouches, gum, lozenges, tablets, and toothpicks. Nearly 1 in 3 participants had ever used an oral nicotine product (1 in 5 13–20-year-olds, 1 in 8 used in past 30 days, 1 in 10 in past 7 days). Flavored nicotine pouches were the most used oral nicotine product in the past 30 days. Favorable perceptions of product marketing is associated with an increased likelihood of buying oral nicotine products. Abstract: Importance: Oral nicotine products such as pouches, lozenges, tablets, gums, and toothpicks are gaining popularity, especially among adolescents and young adults, with increased marketing. Objective: To estimate use patterns of oral nicotine products and likelihood of buying and liking products based on marketing, using a large group of adolescents, young adults, and adults. Design, setting, and participants: A cross-sectional, online survey among U.S. participants (n = 6, 131; ages 13–40 years) was conducted in November-December 2021. Main outcomes and measures: Ever, past-30-day, and past-7-day use, behaviors, and flavors of oral nicotine products. Liking marketing and likelihood of buying specific oral nicotine products (Zyn pouches and Lucy gum) from marketing. Results: Our sample included 2, 025 (33.0%) ever-users, 1, 191 (19.4%) past-30-day users, and 998 (16.3%) past-7-day users of any oral nicotine product. Use patterns by age (in years): ever-users (<21: 816 (22.3%); 21–40: 1, 209 (48.9%)); past-30-day users (<21: 458 (12.5%); 21–40: 733 (29.7%)); and past-7-day users (<21: 383 (10.5%); 21–40: 615 (24.9%)). Across products, 10–18% of participants reported using nicotine strength ranging from 6–10 mg. Fruit, sweet/dessert, alcohol, coffee, and mint were the most used flavors. When shown marketing, ever-users liked and were likely to buy Zyn pouches compared to never users, and participants under 21 years felt equally targeted by Lucy and Zyn marketing. Liking Zyn marketing even a little bit compared to not at all increased the likelihood of buying Zyn pouches across age groups. After observing marketing, participants < 21 years were more likely to buy Zyn if they perceived marketing to contain messages about good tasting flavors (AOR 1.43, 1.09–1.87; 0.009) and helping to feel comfortable in social situations (AOR 1.38, 1.02–1.87; 0.033), and were more likely to buy Lucy if they felt it could be used anywhere (AOR 1.57, 1.05–2.33; 0.026). Conclusions: This study provides a foundation for estimating use, behaviors, flavors, and marketing influence of oral nicotine products in the US and globally. Adolescent and young adult use of oral nicotine products and likelihood of buying products when exposed to marketing highlights the need for expanded tobacco use surveillance, marketing regulations, and counter marketing and educational efforts.